Odpowiedź :
Odpowiedź:
A.5x+4=10
5x=10-4
5x=6 /:5
x= 6/5
B. 3x-5=9
3x=9+5=14/:3
x=14/3=4 2/3
C.-2x+3=7
-2x=7-3
-2x=4 /:-2
x=-2
D.-4x-3=13
-4x=13+3
-4x=16 /:-4
x=-4
a) 5x+4=10
odejmujemy 4 od 10
5x = 10-4
5x = 6 |:5 |dzielimy obu stronnie przez 5|
x = 6/5 = 1 i 1/5
b) 3x-5=9
dodajemy 5 do 9
3x=9+5
3x=14 |:3 |dzielimy obu stronnie przez 3|
x = 14/3 = 4 i 2/3
c) -2x+3=7
odejmujemy 3 od 7
-2x = 7-3
-2x = 4 |:(-2) |dzielimy (-2) obu stronnie|
x = -2
d) -4x-3=13
dodajemy 3 do 13
-4x = 13+3
-4x = 16 |:(-4) dzielimy obu stronnie przez (-4)
x = -4